Predictors of Dementia Among Elderly Residents in Nursing Home - Fitriana, Lisna Anisa; Putri, Suci Tuty; Darmawati, Irma; Andriyani, Septian; Rustiani, Erni; Luu, Puu Taa (Universitas Pendidikan Indonesia, 2023)
Dementia is a syndrome characterized by a decline in intellectual ability that is severe enough to interfere with an elderly person's daily activities. It is still unknown whether specific variables are most frequently linked to dementia in nursing homes, despite the fact that a number of factors are known to cause dementia symptoms. The purpose of this research was to identify the risk factors for dementia in senior citizens residing in assisted living facilities. This study has a cross-sectional design. Eighty-six senior citizens, ages 60 to 90, who resided in two nursing facilities in Bandung and Garut, Indonesia, made up the research sample. The Mini Mental State Examination (MMSE), which has a cut-off score of 24, is used to screen for dementia. Data analysis used the Chi-Square test and logistic regression to examine the link between risk factors and dementia. Education (p = 0.001), BADL (p = 0.014), IADL (p = 0.023), phonemic fluency (p0.001), semantic fluency (p = 0.001), QoL-physical (p = 0.007), QoL-psychological (p = 0.002), QoL-environment (p = 0.001), diabetes (p = 0.013), and depression (p = 0.001) were all significantly correlated with dementia, according to the results. Logistic regression tests showed that education (p = 0.005), phonemic fluency (p = 0.001), and QoL-psychological (p = 0.043) are known to provide the most significant contribution to the occurrence of dementia in senior individuals in nursing homes. It is advised that healthcare professionals offer preventative and promotional actions for senior dementia prediction.